2020
DOI: 10.5194/tc-14-115-2020
|View full text |Cite
|
Sign up to set email alerts
|

Modeling snow slab avalanches caused by weak-layer failure – Part 1: Slabs on compliant and collapsible weak layers

Abstract: Abstract. Dry-snow slab avalanche release is preceded by a fracture process within the snowpack. Recognizing weak-layer collapse as an integral part of the fracture process is crucial and explains phenomena such as whumpf sounds and remote triggering of avalanches from low-angle terrain. In this two-part work we propose a novel closed-form analytical model for a snowpack under skier loading and a mixed-mode failure criterion for the nucleation of weak-layer failure. In the first part of this two-part series we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Collapse height was taken as the mean of the settlement of the slab measured after crack propagation. For the elastic moduli, 220 displacement fields with an increasing crack length prior to crack propagation were used to compare to displacement fields predicted by the mechanical model established by Rosendahl and Weissgraeber (2020a). The optimal set of E sl and E wl was estimated by minimising the residual, with E sl and E wl as free-fitting parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Collapse height was taken as the mean of the settlement of the slab measured after crack propagation. For the elastic moduli, 220 displacement fields with an increasing crack length prior to crack propagation were used to compare to displacement fields predicted by the mechanical model established by Rosendahl and Weissgraeber (2020a). The optimal set of E sl and E wl was estimated by minimising the residual, with E sl and E wl as free-fitting parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The microscopic snow structure and ice properties must be considered for modeling snow mechanical properties and failure initialization. Snow stratigraphy and mechanical properties of snow need to be considered for modeling crack propagation (e.g., [36,38,39]). At the slope-scale, spatial variations of snow stratigraphy and terrain are essential to model avalanche release (e.g., [40,41]).…”
Section: Models In Snow Mechanicsmentioning
confidence: 99%
“…Sigrist and Schweizer (2007) were the first to estimate w f for snow (mean 0.07 J m −2 ), combining field experiments with finite element (FE) modelling. Their method used the critical cut length from a PST and snow micro-penetrometer (SMP) measurements (Schneebeli and Johnson, 1998) to estimate the effective elastic modulus of the slab. Using the same approach, Schweizer et al (2011) reported values an order of magnitude larger, typically around 1 J m −2 .…”
Section: Introductionmentioning
confidence: 99%